Life‐threatening airway obstruction due to retropharyngeal and cervicomediastinal hematomas following transjugular intrahepatic portosystemic shunt procedure for acute variceal bleeding in cirrhosis. - Long Li; Yong Chen (Clinical Case Reports)
Abstract We report a case of life‐threatening airway obstruction due to retropharyngeal‐cervicomediastinal hematomas following transjugular intrahepatic portosystemic shunt or acute variceal bleeding in cirrhosis. Even though this is a rare complication, clinicians should maintain a high index of suspicion and evaluate and treat it promptly to prevent a fatal outcome.